The development push of refugees: Evidence from Tanzania - Maystadt, Jean-François; Duranton, Gilles (International Food Policy Research Institute, 2014)
Every year, thousands of people flee their country of origin to seek protection mainly in neighboring countries. Understanding better the consequences of temporary population shocks on hosting economies should help to guide policies to enhance resilience in emergency situations. This study exploits a 1991–2010 Tanzanian household panel to assess the effects of the temporary refugee inflows originating from Burundi (1993) and Rwanda (1994). We find that the refugee presence has had a persistent and positive impact on the welfare of the local population. We investigate the possible channels of transmission, underscoring the importance of a decrease in transport costs as a key driver of this persistent change in welfare. We interpret these findings as the ability of a temporary shock to induce a persistent shift in the equilibrium through subsequent investments rather than a switch to a new equilibrium in a multiple-equilibrium setting.